Vietnam stock market liberalisation's effect - Khuc, Minh Hieu (2008)
This dissertation examine the effect of stock market liberalisation upon the Vietnam economy and shows the changes during liberalisation period. The stock return and stock return volatility were tested using a generalized autoregressive conditional heteroskedasticity model. The stock return was found to be increased after market was liberalised. The stock return volatility, however show no sign of increasing. The effect upon economic growth, inflation and private investment growth was also determined through standard regression test using various variable. We also show empirical evidence which indicate the stock market become more efficient after it was deregulated. Last but not least, a increase in inflation rate and depreciation in exchange rate were among our findings. Based on this findings, policy implications were also put forward